ANALYZING IMPACT OF US-CHINA TRADE WAR ON INDONESIA STOCK EXCHANGE COMPOSITE INDEX (IHSG) UTILIZING GRAVITY MODEL - Elfan Budi Nugroho, Muhammad
United States and China were biggest trading partner with more than US $600 billion trading value, whereas China had increasingly surplus each year. United States accused China for currency manipulation and intellectual property rights violation to boost China international trade. Under Trump Administration based on United States Trade Representative (USTR) Section 301, United States began to impose tariffs on import products from China. China retaliated for the tariffs imposed by the US government. Indonesia had tendency with China on international trade and foreign direct investment (FDI). Economic events in China would be impacting to Indonesia. The aims of this research were to measure impact of Trump Administration and macroeconomic variables toward Indonesia Stock Exchange Composite Index (IHSG) during US-China trade war. Then, to examine pattern and stock market correlation among United States, China, and Indonesia utilizing Gravity Model. This research using data series during January 2009 – December 2019 period with monthly data. Multiple linear regression analysis with classical assumption test were used in processing data. The results showed that Trump had negative impact, New York Stock Exchange (NYSE) and Shanghai Stock Exchange (SSE) had positive impact, Bank Indonesia Rates had negative impact, The Fed Rates and PBoC Rates had positive impact, USD to IDR had positive impact, RMB to IDR had negative impact, economic distance Jakarta to New York was negative coefficient and Jakarta to Shanghai was positive coefficient. Also, proving Gravity Model in stock market correlation that higher mass (market capitalization) would more influence rather than smaller mass (market capitalization).